ANALISIS TEMUAN PATROLI POLISI HUTAN TERHADAP PERBURUAN SATWA LIAR DI RESORT WAY KANAN, TAMAN NASIONAL WAY KAMBAS - zaqi maula zamzami; Gunardi Djoko Winarno; Yulia Rachma Fitriana; Irwan Sukri Banuwa (Forestry Study Program University Of Mataram, 2021)
Hunting for wildlife in Way Kambas National Park (WKNP) is one of the leading causes of humans and animal conflict. So far, patrol activities are still considered less than optimal because of the decline in animal populations due to frequent hunting. This study aimed to analyze the findings of forest ranger patrols in protecting wild animals from hunting in WKNP. Data collection was carried out by observation, interviews and literature study. The data collected from the literature were then analyzed descriptively qualitatively. The results showed that during patrol activities, the finding of snares was still very much used by hunters and also found elephants that died due to hunting, although the range of forest rangers every year had increased but the number of personnel who did not match the size of the forest area made some areas not can be protected.